Resilience Engineering: A Review of Strategies to Enhance Organizational Robustness in Complex Systems - Ghanbarzadeh, Davood (Management Strategies and Engineering Sciences, 2022)
Resilience engineering has become increasingly vital in the context of managing complex systems that face frequent disruptions and uncertainties. This narrative review systematically examines strategies that organizations can employ to enhance their robustness, focusing on proactive, adaptive, responsive, and transformative approaches. Proactive strategies such as anticipation and preparedness enable organizations to foresee and mitigate potential disruptions. Adaptive strategies, including flexibility and continuous learning, allow organizations to adjust to changing circumstances effectively. Responsive strategies, such as crisis management and redundancy, ensure that operations can be maintained during emergencies. Transformative strategies, particularly innovation and cultural change, foster long-term resilience by encouraging systemic adaptation and evolution. Through a synthesis of existing literature, this review provides a comprehensive understanding of how resilience engineering principles can be applied to enhance organizational robustness in complex environments. The findings have significant implications for both researchers and practitioners, offering insights into the development of more resilient organizational structures.